Pengaruh Alkalisasi Nib Kakao terhadap Kandungan Kimia dan Warna Bubuk Kakao - Eko Heri Purwanto; Tajul Iflah; Asif Aunillah (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Purwanto EH, Iflah T, Aunillah A. 2020. The effect of cocoa nib alkalization on chemical content and color of cocoa powder. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xxx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The natural processing of cocoa beans into cocoa powder tends to produce a powder with a pale color that is less attractive. One of the treatments at this stage of the process carried out to improve the quality and appearance of cocoa powder is alkalization. Alkalization is done by adding alkaline compounds to the cocoa nibs with immersion. This study aim is to determine the effects of alkalization treatments on the chemical content and color of cocoa powder. The study was conducted at Indonesian Industrial and Beverages Crop Research Institute from January to December 2019. The alkalization treatment used four different types of alkalis, namely K2CO3, KOH, Na2CO3 and NaOH with three different concentrations, namely 1%, 2%, and 3%. The parameters observed included moisture content, ash content, fat content, pH and color intensity. The results showed that the alkalization treatment had a significant effect on all variables except moisture content and fat content. The higher degree of alkalization, the higher ash content and pH, while the colour intensity (L *, a * and b * values) was lower.